Ompok brevirictus, a new catfish (Teleostei: Siluridae) from Sumatra - Ng, Heok Hee; Hadiaty, Renny K. (Zootaxa, 2009)
Ompok brevirictus, a new species of silurid catfish is described from the short coastal rivers draining the western face of the Leuser Mountain Range and debouching into the Indian Ocean in Nangroe Aceh Darussalam province, northern Sumatra. Ompok brevirictus can be distinguished from Ompok siluroides and O. miostomus, the Southeast Asian congeners that it most resembles, in having an evenly convex predorsal profile (vs. with a concavity posterior to orbit) and a more prominent lower jaw that is more broadly curving. Ompok brevirictus additionally differs from O. siluroides in having the mouth rictus separated from the anterior orbital margin by a distance of one-third (vs. less than one-third) eye diameter (4.2–5.2% HL vs. 3.2–3.7) and lacking (vs. with) a distinct dark wedge-shaped spot on the base of the caudal fin. The identity of the Southeast Asian material usually identified as O. bimaculatus is also clarified. Ompok bimaculatus is restricted to the Indian subcontinent and Myanmar in this study; the Southeast Asian material previously identified as conspecific is hereby referred to either O. siluroides or O. miostomus.